Forest fragmentation impacts the seasonality of Amazonian evergreen canopies - Nunes, Matheus Henrique; Camargo, José Luís Campana; Vincent, Grégoire; Calders, Kim; Oliveira, Rafael S.; Huete, Alfredo; Mendes de Moura, Yhasmin; Nelson, Bruce; Smith, Marielle N.; Stark, Scott C.; Maeda, Eduardo Eiji (Nature communications, 2022)
Predictions of the magnitude and timing of leaf phenology in Amazonian forests remain highly controversial. Here, we use terrestrial LiDAR surveys every two weeks spanning wet and dry seasons in Central Amazonia to show that plant phenology varies strongly across vertical strata in old-growth forests, but is sensitive to disturbances arising from forest fragmentation. In combination with continuous microclimate measurements, we find that when maximum daily temperatures reached 35 °C in the latter part of the dry season, the upper canopy of large trees in undisturbed forests lost plant material. In contrast, the understory greened up with increased light availability driven by the upper canopy loss, alongside increases in solar radiation, even during periods of drier soil and atmospheric conditions. However, persistently high temperatures in forest edges exacerbated the upper canopy losses of large trees throughout the dry season, whereas the understory in these light-rich environments was less dependent on the altered upper canopy structure. Our findings reveal a strong influence of edge effects on phenological controls in wet forests of Central Amazonia. Even evergreen tropical forests can have seasonal dynamics, which may be sensitive to disturbance. Here, the authors combine high-resolution remote sensing observations and microclimate data to show that forest fragmentation impacts canopy phenology dynamics in the Amazon forest.